Testing Quiet Life Hypothesis in the Banking Sector (Journal of Economic Research & Business Administration, 2020)
The current research continues the series of studies aimed to analyze the issues in regards to bankefficiency in the Baltic banking market. The goal of the current paper is to empirically test the QuietLife Hypothesis (QLH) and to investigate the relationship between market concentration and efficiencyin the banking sector of Latvia, Lithuania and Estonia. Two QLH-related hypotheses are stated for theresearch purposes.To achieve the established goal, the authors run a multiple regression analysis, using efficiency ofan individual bank as a dependent variable. In turn, independent variables include market concentrationproxied by Herfindahl-Hirschman Index (HHI) and bank-specific measures, such as market share, profitabilityand productivity.Efficiency scores for individual banks were estimated applying Data Envelopment Analysis (DEA).Study is based on the sample data of 33 banks operating in the Baltic countries, covering the period of2007-2013 (227 observations). Data processing was made with application of DEAFrontier and SPSSsoftware.In the result of the performed analysis the stated hypotheses are rejected. Thus, there is no empiricalevidence that market power, and consequently, market concentration in the Baltic banking sectornegatively impacts the efficiency of individual banks.At the same time, researchers should pay special attention to two conceptual issues in the process ofdeveloping methods for regulating Bank liquidity: the size of the Bank’s equity capital and the conditionsof the external environment.